Farm operators’ behavioural intention towards synthesis pesticide purchase in Malaysia - Lai, Woet-Jian; Goh, Yen-Nee; Ting, Mao-Seng (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper analyses factors influencing Malaysian farm operators’ behavioural intention towards synthesis pesticide purchase. The research framework proposed was empirically tested using data collected from 118 farm operators in Malaysia. The result from the finding suggested that supplier’s flexibility is significantly and positively affect Malaysia farm operators’ behavioural intention towards synthesis pesticide purchase. Meanwhile, the routine purchase is significantly but negatively affecting Malaysia farm operators’ behavioural intention towards synthesis pesticide purchase. However, the trust did not serve any moderating effect between independent variables and the dependent variable. The result of this study allows authorities such as the Department of Agriculture and the Pesticide Board of Malaysia to have better clarity in strategised their resources to counter the illegal pesticide issue. Marketing practitioners from the agrochemical company would benefit from this result to align their marketing strategy for their pesticide based on farm operators’ behavioural intention of purchase.